Tathwîr Namûdzaj al-Ta’allum al-Iliktrûnî li Mâdah al-Lughah al-‘Arabiyah al-Qâim ‘ala al-Web fî al-Madrasah al-Mutawasithah al-Islâmiyah bi Jakarta - Jubaidah, Siti; Bahtiar, Ihwan Rahman; Salamah, Faqiha Nibros (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2022)
This study aimed to develop the web-based e-learning model for the Arabic language material in the Islamic Middle School 25 Jakarta. This research used the R&D method in the term of the Dick and Carrie model. The result of this study is reflected from the materials expert's approval of the e-learning model for the Arabic course based on the web is 80%. This result indicates a very good evaluation of the test on the students. The result of the media expert's approval of the e-learning model for the Arabic language course based on the web is 95%. This result indicates a very good evaluation of the test on the student. E-learning is considered a new method of learning that focuses strongly on information centers and has become an important part of the field of academic universities added to the situation of our country that is currently exposed to the COVID-19 viruses, the role of Internet-based learning as support for the learning process becomes very important.